Patients with Cardiorenal Syndrome Revealed Increased Neurohormonal Activity, Tubular and Myocardial Damage Compared to Heart Failure Patients with Preserved Renal Function - Palazzuoli, Alberto (Cardiorenal Med, 2014)
BACKGROUND: Cardiorenal syndrome (CRS) is associated with increased cardiovascular morbidity and mortality; still, its biomarker pattern has been poorly evaluated so far. The aim of this study was to measure the inflammatory activation, neurohormonal status and kidney and myocardial damage in patients with CRS compared to patients with heart failure (HF) without renal impairment (RI). METHODS: We analyzed 246 patients on the basis of renal function (group 1: 120 HF patients without RI; group 2: 126 CRS patients). In each group, interleukin-6, tumor necrosis factor-α, B-type natriuretic peptide (BNP), neutrophil gelatinase-associated lipocalin (NGAL), troponin T (TnT), osteoprotegerin and blood urea nitrogen (BUN) were measured. The diagnostic power of all laboratory parameters to detect CRS was evaluated by the receiver operating characteristic (ROC) curve and logistic regression analysis. RESULTS: A significant increase in BNP [626.4 pg/ml, confidence interval (CI) 518-749 vs. 487.8 pg/ml, CI 411-578; p < 0.05], NGAL (156 ng/ml, CI 129-186 vs. 89.1 ng/ml, CI 72-109; p < 0.0001), BUN (108.9 mg/dl, CI 98-120 vs. 51 mg/dl, CI 46-55; p < 0,0001) and TnT (0.62 ng/ml, CI 0.51-0.75 vs. 0.21 ng/ml, CI 0.15-0.28; p < 0.001) was seen in CRS patients compared to HF patients without RI. ROC curve analysis showed that only NGAL, BUN, BUN/creatinine ratio and TnT can discriminate patients with CRS from patients without RI. CONCLUSIONS: In CRS patients, renal tubular damage and neurohormonal and cardiac injury activation are increased compared to patients without RI. The current biomarker pattern could be used for an early diagnosis of RI in acute and chronic HF.